2019
DOI: 10.1111/apm.12944
|View full text |Cite
|
Sign up to set email alerts
|

IL‐2/IL‐6 ratio correlates with liver function and recovery in acute liver injury patients

Abstract: Acute liver injury can result from a number of different diseases. Inflammatory cytokines are known to be involved in the development of this condition; however, their precise roles and effects on liver function remain unclear. The goal of this study was to determine the relationship between serum cytokine levels and both the severity of liver damage and recovery in acute liver injury. We enrolled 100 patients with acute liver injury caused by drug application who were hospitalized from September 2012 to Septe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Steuerwald et al claimed that low serum levels of IL-9 and IL-17 predict early death caused by drug-induced liver injury [26]. Sun's study has confirmed that the change of IL-2/IL-6 ratio is often used as an evaluation index of liver function recovery in patients with acute liver injury [27]. Data from this study suggested that early IL-6 level is an important marker of advanced liver function in pregnant women with hepatitis B.…”
Section: Discussionmentioning
confidence: 98%
“…Steuerwald et al claimed that low serum levels of IL-9 and IL-17 predict early death caused by drug-induced liver injury [26]. Sun's study has confirmed that the change of IL-2/IL-6 ratio is often used as an evaluation index of liver function recovery in patients with acute liver injury [27]. Data from this study suggested that early IL-6 level is an important marker of advanced liver function in pregnant women with hepatitis B.…”
Section: Discussionmentioning
confidence: 98%
“…However, uncontrolled immunity, triggered by acute phase factors, can lead to liver injury [9]. IL-6 induces the expression of IL-17 and promotes hepatocyte apoptosis, thus aggravating liver damage [10]. Li's study suggests that reducing IL-6 is beneficial to attenuating ethanol-induced liver injury [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-6 (IL-6) plays a key role in the occurrence and development of liver diseases and the effects vary in different periods of disease progression [10]. At the early stage of ALD, high levels of IL-6 in serum suggest a good prognosis, and in hepatocytes, its downstream signal transducer and activator of transcription 3 (STAT3) activation ensues to regulate various hepatocyte-protective genes to reduce inflammatory response; however, high levels of serum IL-6 serve as a poor prognostic indicator for patients at the terminal stage of ALD [11,12]. Therefore, targeting IL-6 and its related signaling pathways in the liver could hint at a new target for the diagnosis and treatment of liver disease.…”
Section: Introductionmentioning
confidence: 99%